Analysis of Inventory Recording in Church-Owned Enterprises (BUMG BNKP) BNKP LPLG Unit - Adil Setia Zebua; Sophia Molinda Kakisina; Idarni Harefa; Dedi Irawan Zebua (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyze the inventory recording practices implemented by the Church-Owned Enterprise (BUMG BNKP) Unit LPLG BNKP, which operates as both a printing unit and a distributor of church service products. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. Findings reveal that although the unit applies the FIFO method in managing inventory flow—where the first goods received are the first to be sold—the existing stock card format is not fully aligned with PSAK No. 14. Key gaps include the absence of recorded purchases, sales returns, and purchase returns, resulting in inconsistencies between administrative records and physical inventory. Several challenges were also identified, such as delayed data entry, discrepancies between warehouse stock and administrative reports, and non-integrated documentation formats. The study proposes improvements to the stock card format by integrating all types of inventory transactions into a single record-keeping system based on FIFO and PSAK No. 14. Implementing these improvements is expected to strengthen internal control, enhance accuracy in financial reporting, and reduce the risk of losses due to inventory errors.